Repeated presentation of children and adolescents to the emergency department following self‐harm: A retrospective audit of hospital data. (26th February 2020) - Summers, Peter; O'Loughlin, Rachel; O'Donnell, Sinead; Borschmann, Rohan; Carlin, John; Hiscock, Harriet
Abstract: Objective: To examine re‐presentation rates for self‐harm in patients aged 0–18 years to the ED of a tertiary paediatric hospital in Melbourne, Australia, and associated patient, family and hospital presentation factors. Methods: Data for presentations from 1 July 2016 to 31 December 2018 were extracted from the hospital's electronic medical record system. Self‐harm presentations were identified through automated, rule‐based coding and manual review of medical notes. Re‐presentation rates for intervals up to 12 months were estimated using survival methods with risk factor associations examined using Cox regression. Results: Of the 952 presentations for self‐harm after 1 January 2017, 529 were considered first presentations. An estimated 15% (95% confidence interval [CI] 12–19), 20% (95% CI 17–24) and 23% (95% CI 19–27) re‐presented for self‐harm within 3, 6 and 12 months, respectively. A total of 82% of all presentations were for girls. Patients were more likely to re‐present if they had previously presented more than once, were flagged as vulnerable (hazard ratio [HR] 1.35, 95% CI 1.08–1.68), had a history of substance abuse (HR 1.30, 95% CI 1.03–1.64), were female (HR 1.43, 95% CI 0.92–2.21), had self‐cut (HR 1.38, 95% CI 0.96–1.97), had an aggressive behaviour response team called during the visit (HR 1.44, 95% CI 0.85–2.45) or had a history of depression (HR 1.27, 95% CI 0.99–1.63). Conclusions: In this paediatric ED, almost one in four patients re‐presented with self‐harm within 12 months. Previous presentations and other factors were associated with risk of re‐presenting, although no factor was strongly predictive. Future research might examine the generalisability of these findings across settings and explore strategies for prevention. Abstract : The number of children and young people (0–19‐year‐olds) presenting to Victorian EDs for mental health problems has risen sharply since 2008, but the reasons for this are unclear. Anecdotally, children and adolescents who present with self‐harm re‐present a number of times, which may be contributing to the rise. Understanding these patients' use of ED services and associated risk factors, may allow us to focus care where it will be of greatest benefit, support them better once they have presented to the ED and direct them to more appropriate care in the community. For the first time in Australia, we examined re‐presentation rates to ED for children and adolescents who had self‐harmed over a 2‐year period.